General English Pre-Intermediate Implementation: Learning Resources for Local and International Students - Ilantri, Yuyun; Muslim, Ahmad Bukhori; Gandana, Isti Siti Saleha (Institut Agama Islam Negeri (IAIN) Curup, 2024)
The study aims to identify the learning resources that are employed in a language center at Indonesia's oldest university both for local and international foreign students. The study uses descriptive qualitative as the main approach through interviews with an English teacher coordinator and learning resources documentation analysis. The interview data and documents were analyzed through thematic analysis. The findings revealed that there is consideration of both types of classes in the same class, the study findings indicate that the instructional materials used for them are typically similar. Teachers still face difficulties since international students must attend classrooms where the bulk of the students speak Indonesian even though they still struggle to understand the language. In addition, this Pre-Intermediate program makes use of digital instructional resources. This is done since textbook-based teaching materials are viewed as being out of date and becoming less and less relevant to modern advancements. To help teachers improve their lesson plans and make them more relevant in the future, it is believed that the research's findings would be useful as evaluation material.